Causes of the Primary Urinary Bladder Stones in Children and their Prevension in Population of Dera Ismail Khan, KPK, Pakistan - Muhammad Seerwan, Imran Hyder, Rana Ata ur Rehman, Hammad Shafi, Ghazi Khan, Ali Shandar Durrani, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: History of the stone disease dates back to ancient Egyptian era. Stones involving the urinary bladder are usually 5% of the disease burden. In the Europe and America prevalence of primary bladder stones is decreased significantly in the recent ere but it is still common in developing nations including Pakistan. Materials and methods: We retrospectively collected the data from the parents of the affected children during the follow up. We took the detailed interview regarding the amount of water used by the child, amount and type of milk given and type of food given to the child. Results: We were operated 148 children with the bladder stones in the department of urology DHQ-TH D.I. Khan. There were 117 (79.05%) boys and 31 (20.94%) girls. The children below the 5 years of age were 101 (68.24%).139 (94%) of the patients belonged to the rural areas of the D.I. Khan. There were 132 (89.19%) children those were malnourished. The duration of breast feeding was approximately 12 to 15 months. They started the weaning at 7–8 months with the wheat bread and tea and also added the potatoes in the diet. With increasing age they added the pulses and the vegetables. Only 10.81% of the parents given the child meat, eggs and milk in the diet. 104 (70.27%) of the children were dehydrated. Conclusion: The risk factors for primary bladder stones in the children are multifactorial. Important factors are dehydration, low protein diet and foods deficient in phosphate contents. Keyword: Primary Bladder Stones; Children; Pakistan; Risk Factors.